FIBER-REINFORCED COMPOSITE MOLDING - NAGATA KOSUKE (2023)
To provide a fiber-reinforced composite molding which is excellent in mechanical characteristics such as flexural strength and shear strength, and long-term durability of the mechanical characteristics, flame retardancy, and appearance.SOLUTION: A fiber-reinforced composite molding is a composite molding composed of fibers for reinforcement and a thermoplastic resin, wherein the thermoplastic resin is a resin composition containing 70-99 pts.wt. of (A) a polycarbonate resin (component A), and 30-1 pts.wt. of (B) phosphazene (component B) containing 98.5 mol% or more of a phosphazene cyclic trimer, and a content of the fibers for reinforcement is 15-400 pts.wt. with respect to 100 pts.wt. of the resin component composed of the component A and the component B of the thermoplastic resin.SELECTED DRAWING: Figure 2 【課題】曲げ強度、せん断強度等の機械特性およびこれらの長期耐久性、難燃性ならびに外観に優れる繊維強化複合成形体を提供する。【解決手段】補強用繊維と熱可塑性樹脂からなる複合成形体であって、熱可塑性樹脂が、（Ａ）ポリカーボネート樹脂（Ａ成分）７０～９９重量部および（Ｂ）ホスファゼン環状三量体を９８．５ｍｏｌ％以上含有するホスファゼン（Ｂ成分）３０～１重量部を含有する樹脂組成物であり、かつ補強用繊維の含有量が、熱可塑性樹脂のＡ成分とＢ成分とからなる樹脂成分１００重量部に対して、１５～４００重量部であることを特徴とする繊維強化複合成形体。【選択図】図２